Studi Komparasi Karakteristik Asap Cair Hasil Pirolisis dari Kulit Durian, Pelepah dan Tandan Kosong Sawit dengan Pemurnian Secara Distilasi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Liquid smoke is one of the modern methods of food preservation. It made from biomass containing cellulose, hemicellulose and lignin. The purpose of this research was to generate and compare the characteristics of liquid smoke results from pyrolysis feedstock durian shell, EFB and palm midrib and distillation refining. The method is carried out every feedstock in the pyrolysis temperature range of 300-350 °C and distilled temperature at of 175 °C. Then, performed analysis of the characteristics of liquid smoke compounds using GC/MS and test pH using a pH meter. The yield of liquid smoke pyrolysis results of each feedstock is durian shell 42.474%; 49.647% EFB and palm midrib 44.66%. From the analysis of GC/MS, acetic acid has the highest percent area among 16 dominant compounds in liquid smoke of pyrolysis results and among 14 dominant compounds after distillation. Percent acetic acid in the area of liquid smoke each feedstock pyrolysis results changed after the distillation of durian shell 54.17% to 62.8%; EFB 48.83% to 74.39% and palm midrib 52.19% to 41.14%. The percent area of phenolic compounds that act as antioxidants skin durian is 1.38% to 2.72%; EFB 5.28% to 6.56% ; palm midrib 9.12 % to 5.84 %. Liquid smoke pH values obtained after distillation is the durian shell 3.8; EFB 3.5 and 3.4 of palm midrib . Keywords :, durian shell, EFB, liquid Smoke, palm midrib, pyrolysis